Assessment of a Safe Work-Impulse for Farmers: A Case Study of Ilara-Mokin, Ondo State, Nigeria - Abiola, Oluranti; Ogedengbe, Temitayo; Joseph, Ojotu; Omonayin, Oluwakayode (Journal of Advanced Industrial Technology and Application, 2025)
The study measured the heart rates of farmers in Ilara-mokin while they carried out a few regular farm tasks with a view to create a safe work-impulse chart for farmers in that locality. This is expected to provide the information required for the adequate use of muscular force and the prevention of fatigue or physical exertion, during farming. Farmers who were available and were willing to participate in the study were divided into five age groups, such as below 25, 25-34, 35-44, 45-54, and above 54 years, and their heart rates were monitored and recorded under three different categories of farm activities or load (light load, medium load, and heavy load) using a premium pressure monitor with comfit cuff. The time and the heart rate at which the farmers feel a sense of discomfort or tiredness were used to evaluate the safe work-impulse for each category of activities. The result shows that farmers below 45 years of age record a work-impulse of about 9.0M kNs and 7.2H kNs for medium and heavy loads respectively while older farmers manage to sustain medium and heavy loads at a work-impulse of 7.2M kNs, 5.4M kNs and 9.0M kNs, 5.4M kNs respectively. In conclusion, the study revealed that while farmers of any age can handle a light activity for a longer period of time than 18 minutes, they may not be able to sustain heavier loads for a longer period.